International Normalized Ratio-to-Albumin Ratio as a Novel Marker of Upper Gastrointestinal Bleeding Severity. (13th October 2022) - Choi, Jeongwoo; Lee, Je Seop; Lee, Solmoon; Kim, Yong Won; Lee, Yoonsuk; Kim, Tae Youn
Abstract : Introduction . Upper gastrointestinal bleeding (UGIB) is a potentially life-threatening gastrointestinal emergency, and effective management depends on early risk stratification. The Glasgow–Blatchford and Rockall scores are commonly used prognostic measures for UGIB, although these scoring systems are relatively difficult to apply in early emergency settings. AIMS65 with five items, albumin, international normalized ratio, mental status, systolic blood pressure, and age (>65 years), showed efficacy in predicting long-term hospitalization and mortality. This study aimed to investigate the usefulness of the prothrombin time-international normalized ratio-to-albumin ratio (PTAR) in the emergency room for early UGIB risk stratification. Methods . We retrospectively examined patients who visited a tertiary academic hospital's emergency department (ED) with UGIB as the chief presentation between January 2019 and December 2020. The cutoff values and diagnostic accuracies of the PTAR, Glasgow–Blatchford score, AIMS65 score, pre-endoscopy, and complete Rockall score were analyzed, and the performance of the PTAR was compared with that of other risk stratification methods. In total, 519 patients were enrolled: 163 patients were admitted in the intensive care unit (ICU) and 35 died during admission. Multiple logistic regression analyses confirmed the association of the PTAR with ICU admission and mortality. The adjusted odd ratio (aOR) of the PTAR for ICU admission care was 8.376 (2.722–25.774), and the aOR of the PTAR for mortality was 27.846 (8.701–89.116). Conclusions . The PTAR measured in the ED is an independent factor related to ICU admission and mortality in patients with UGIB. Using ED blood laboratory results, which are reported relatively quickly and are easy to acquire and calculate, the PTAR can be used as a risk stratification marker in the early emergency setting.